Development of ratiometric sensing and white light-harvesting materials based on all-copper nanoclusters. Issue 3 (17th December 2018) - Li, Dan; Wang, Guannan; Peng, Yongjin; Chen, Zhenhua; Gao, Xianhui; Cheng, Liming; Mei, Xifan
Abstract : Herein, we developed a special strategy for the fast sensitization of red emitting copper nanoclusters with the assistance of green emitting copper nanoclusters. Abstract : Herein, we developed a special strategy for the fast sensitization of red emitting copper nanoclusters with the assistance of green emitting copper nanoclusters. Compared to most previous methods based on AIE, which do not maintain the water solubility or tiny size of nanoclusters, the charming features of the copper nanoclusters were retained after the fabrication. Furthermore, the product was employed for the detection of sulphide, which revealed its ratiometric sensing ability in water since the ratio of the intensity change for green and red emission was related to the sulphide concentration. In addition, after the addition of Zn 2+, the green and red emission was either enhanced or quenched via the corresponding mechanism. This enables the facile fabrication of promising white light-harvesting materials since the species of the emitting color can be simply tuned.